High-rate sodium ion battery positive electrode material and preparation method thereof

By introducing Mg and/or Ca elements into the sodium ferric sulfate material and compounding it with flash graphene, the problem of poor conductivity of sodium ferric sulfate material is solved, and excellent performance and long cycle stability are achieved at high magnifications.

CN119542400APending Publication Date: 2025-02-28SHANXI UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411740063.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The intrinsic conductivity of sodium ferrous sulfate material is poor, resulting in poor capacity and circulation performance at high magnifications, making it difficult to stabilize and maintain efficient transmission of sodium ions.

Method used

By introducing Mg and/or Ca elements, modifying the lattice of sodium ferrosulfate, combining with the conductive network of flash graphene, a solid phase physical ball mill and low-temperature calcination method are used to prepare sodium ferromagnesium sulfate (and/or calcium) sodium and flash graphene composite materials.

Benefits of technology

The conductivity of sodium ferric sulfate material is significantly improved, excellent rate performance and long cycle stability are obtained, and the efficient transmission of sodium ions can be stably maintained at high magnifications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119542400A_ABST
    Figure CN119542400A_ABST
Patent Text Reader

Abstract

The invention discloses a high-rate sodium-ion battery positive electrode material and a preparation method thereof, and belongs to the technical field of sodium-ion battery electrodes. Aiming at the problem that the capacity and the cycle performance of the current sodium ferric sulfate material under high magnification are still not ideal enough, ferrous sulfate heptahydrate is roasted in an inert atmosphere to obtain anhydrous ferrous sulfate. Anhydrous FeSO4, anhydrous Na2SO4, anhydrous MgSO4 and / or anhydrous CaSO4 and the flash graphene are subjected to ball-milling mixing reaction according to a certain mass ratio, and a roasting precursor is obtained. And sintering in a rotary tube furnace protected by inert atmosphere to obtain the single-crystal magnesium ferric sulfate (and / or calcium) sodium composite positive electrode material. Mg and / or Ca elements are doped and introduced, so that a crystal structure of a sodium ferric sulfate crystal is distorted to a certain extent, the delocalization capability of outer layer electrons of Fe atoms is improved, meanwhile, the forbidden bandwidth of sodium ferric sulfate is reduced, and the conductivity of the material is obviously improved. The rate characteristic of the sodium ferric sulfate positive electrode material is greatly improved, and the method is particularly suitable for being applied to the field of large-scale energy storage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sodium ion battery electrodes, and in particular relates to a high-rate sodium ion battery positive electrode material and a preparation method thereof. Background Art

[0002] As the proportion of renewable energy in the national economy continues to rise, the development of large-scale energy storage systems that match it has also received more and more attention. As an electrochemical energy storage device with low raw material cost and high safety, sodium-ion batteries have become one of the most promising systems in the field of large-scale energy storage. As a key component of the battery, the positive electrode material has a huge impact on the performance and cost of the entire sodium-ion battery. At present, the positive electrode route of sodium-ion batteries mainly includes transition metal layered oxides, Prussian blue analogs, polyanion compounds, etc. Among them, polyanion-type sodium iron sulfate positive electrode materials have attracted great attention from researchers due to their low material cost, high operating voltage (~3.8V) and stable cycle performance, but due to the poor intrinsic conductivity of sodium iron sulfate materials, the rate performance of the material is not good. High rate performance is a key rigid demand for large-scale energy storage systems, so how to improve the rate performance of sodium iron sulfate materials is the key to whether they can be further applied in the field of large-scale energy storage.

[0003] Studies have shown that compounding with highly conductive carbon materials can solve the conductivity problem of sodium iron sulfate to a certain extent. Current research is mostly based on this perspective, such as (CN 118851274 A, CN 118472225A, Science Bulletin, 2023, 68: 1894–1903, Nature Communications, 2023, 14: 3701). Using these existing technologies, although it is possible to synthesize sodium iron sulfate composite materials with significantly improved conductivity and good cycle stability. However, the capacity and cycle performance of the material at high rates are still not ideal. The main reason is that the composite of carbon materials and sodium iron sulfate crystals belongs to contact composites, and does not change the problem of poor intrinsic conductivity of sodium iron sulfate crystal particles. Therefore, at higher rates, it is difficult for the material to stably maintain efficient transmission of sodium ions. Summary of the invention

[0004] In view of the problem that the capacity and cycle performance of the current sodium ferric sulfate material at high rate are still not ideal, the present invention provides a new single crystal magnesium ferric sulfate (and / or calcium) sodium composite electrode material and a preparation method thereof, and adopts a simple solid phase physical ball milling and low-temperature calcination method to prepare a magnesium ferric sulfate (and / or calcium) sodium single crystal and flash graphene composite material, and through Mg and / or Ca doping, the intrinsic conductivity of the sodium ferric sulfate crystal is greatly improved, and a sodium ion battery composite positive electrode material with excellent rate performance is obtained.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] A high-rate sodium ion battery positive electrode material, comprising magnesium iron sulfate (and / or calcium) sodium single crystal particles and flash graphene; the chemical formula of the magnesium iron sulfate (and / or calcium) sodium is: Na 2+2x M y Fe 2-x-y (SO4)3, wherein x ranges from 0.25 to 0.45, y ranges from 0.05 to 0.6, and M is Mg and / or Ca element.

[0007] Furthermore, in the chemical formula of the sodium magnesium (and / or calcium) ferrous sulfate, when M is the coexistence of Mg and Ca, the molar fractions of Mg and Ca in M ​​are: Mg 0.01-0.99, calcium 0.99-0.01.

[0008] Furthermore, the mass ratio of the sodium magnesium iron sulfate (and / or calcium) single crystal particles and the flash graphene is: 85-97% of the sodium magnesium iron sulfate (and / or calcium) single crystal particles and 3-15% of the flash graphene.

[0009] Furthermore, the Joule heat treatment temperature of the flash graphene is between 3100 and 3300 K, and the time is less than 1 second.

[0010] A method for preparing a high-rate sodium ion battery positive electrode material comprises the following steps:

[0011] S1, subjecting ferrous sulfate heptahydrate to heat treatment in an inert atmosphere tube furnace to obtain anhydrous ferrous sulfate;

[0012] S2, ball milling anhydrous ferrous sulfate, anhydrous sodium sulfate, anhydrous magnesium sulfate and / or anhydrous calcium sulfate and flash graphene in an inert atmosphere ball mill for 4 to 15 hours to obtain a calcined precursor;

[0013] S3, placing the calcined precursor in an inert atmosphere tube furnace at 320-380° C. for calcination, with a heating rate of 1.5-2° C. / min and a calcination time of 6-15 h to obtain a sodium iron magnesium (and / or calcium) sulfate composite electrode material.

[0014] Furthermore, in step 1, the heat treatment temperature is 250° C. and the time is 4 to 12 hours.

[0015] Furthermore, in the step 2, the gas filled in the inert atmosphere ball milling jar is argon or nitrogen, and the ball milling time is 4 to 12 hours.

[0016] Compared with the prior art, the present invention has the following advantages:

[0017] (1) In view of the problems of poor intrinsic conductivity and low rate performance of the current sodium ferric sulfate electrode materials, the present invention creatively introduces Mg and / or Ca elements to modify the sodium ferric sulfate lattice. The successful doping of Mg and / or Ca can change the electron cloud distribution of Fe atoms in the lattice, improve the delocalization ability of Fe outer electrons, and effectively reduce the band gap width of sodium ferric sulfate, so that its conductivity is significantly improved. Combined with the good conductive network of flash-evaporated graphene, the conductivity of the composite material can be significantly improved.

[0018] (2) The electrode material provided by the present invention has the advantages of simple and convenient preparation method, low cost, good rate performance, good cycle stability (>6000 times), etc., and has strong market competitiveness in the field of large-scale energy storage applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a charge and discharge curve diagram corresponding to the sodium ion battery prepared from the sodium magnesium iron sulfate composite positive electrode material obtained in Example 1 of the present invention.

[0020] Figure 2 This is a rate performance diagram corresponding to the sodium ion battery prepared from the sodium magnesium iron sulfate composite positive electrode material obtained in Example 2 of the present invention.

[0021] Figure 3 This is the long cycle diagram corresponding to the sodium ion battery prepared by the sodium magnesium iron sulfate composite positive electrode material obtained in Example 2 of the present invention.

[0022] Figure 4 The XRD pattern of the sodium magnesium iron sulfate composite positive electrode material obtained in Example 3 of the present invention.

[0023] Figure 5 This is a scanning electron microscope image corresponding to the sodium magnesium iron sulfate composite positive electrode material obtained in Example 3 of the present invention.

[0024] Figure 6 This is a transmission electron micrograph of the sodium magnesium iron sulfate composite positive electrode material obtained in Example 3 of the present invention.

[0025] Figure 7 This is a rate performance diagram corresponding to a sodium ion battery prepared from the sodium calcium iron sulfate composite positive electrode material obtained in Example 4 of the present invention.

[0026] Figure 8 This is a long cycle diagram at a high current of 100C corresponding to the sodium ion battery prepared from the magnesium-calcium-sodium iron sulfate composite positive electrode material obtained in Example 6 of the present invention. DETAILED DESCRIPTION

[0027] In order to gain a deeper understanding of the present invention, we will provide a comprehensive and detailed description of the present invention. However, the present invention has multiple implementations and is not limited to the specific examples listed herein. The presentation of these examples is intended to deepen the comprehensive understanding of the disclosure of the present invention.

[0028] Example 1

[0029] S1, heat-treat 47.26 g of ferrous sulfate heptahydrate in an inert atmosphere tube furnace at 250° C. for 6 h to obtain 25.84 g of anhydrous ferrous sulfate.

[0030] S2, 25.84 g of anhydrous ferrous sulfate, 17.75 g of anhydrous sodium sulfate, 0.6 g of anhydrous magnesium sulfate and 1.37 g of flash graphene are ball-milled in an inert atmosphere ball mill for 9 h to obtain a calcined precursor.

[0031] S3, placing the calcined precursor in an inert atmosphere tube furnace for calcination at 350°C, with a heating rate of 1.8°C / min and a calcination time of 9h to obtain a sodium iron magnesium sulfate composite electrode material, wherein the sodium iron magnesium sulfate molecular formula is Na 2.5 Mg 0.05 Fe 1.7 (SO4)3, the flash graphene content is 3.00wt%.

[0032] The sodium iron magnesium sulfate composite positive electrode material obtained above is used to prepare a sodium ion battery. The charge and discharge curve corresponding to the sodium ion battery is shown in the figure below. Figure 1 As shown in the figure, it can be seen that the discharge specific capacity of the material can still reach more than 90 mAh / g at a current density of 0.5C (1C=120 mAh / g).

[0033] Example 2

[0034] S1, heat-treat 26.41 g of ferrous sulfate heptahydrate in an inert atmosphere tube furnace at 250° C. for 4 h to obtain 14.44 g of anhydrous ferrous sulfate.

[0035] S2, 14.44 g of anhydrous ferrous sulfate, 20.59 g of anhydrous sodium sulfate, 7.2 g of anhydrous magnesium sulfate and 1.96 g of flash graphene are ball-milled in an inert atmosphere ball mill for 6 h to obtain a calcined precursor.

[0036] S3, placing the calcined precursor in an inert atmosphere tube furnace for calcination at 360°C, with a heating rate of 1.8°C / min and a calcination time of 9h to obtain a sodium magnesium ferric sulfate composite electrode material, wherein the sodium magnesium ferric sulfate molecular formula is Na 2.9 Mg 0.6 Fe 0.95 (SO4)3, the flash graphene content is 4.44wt%.

[0037] The sodium ferric magnesium sulfate composite positive electrode material obtained above was used to prepare a sodium ion battery. The corresponding rate performance diagram is shown in Figure 2 As shown, the results show that the material still has a cycle capacity of more than 65mAh / g at a large rate of 100C; the long cycle diagram corresponding to the sodium ion battery is shown in Figure 3 As shown, the results show that the capacity retention rate of the material reaches more than 90% after 6000 cycles at a high current of 50C, and it has excellent high-rate cycle stability.

[0038] Example 3

[0039] S1, heat-treat 41.70 g of ferrous sulfate heptahydrate in an inert atmosphere tube furnace at 250° C. for 6 h to obtain 22.80 g of anhydrous ferrous sulfate.

[0040] S2, 22.80 g of anhydrous ferrous sulfate, 18.46 g of anhydrous sodium sulfate, 2.4 g of anhydrous magnesium sulfate and 3.29 g of flash graphene were ball-milled in an inert atmosphere ball mill for 4 h to obtain a calcined precursor.

[0041] S3, placing the calcined precursor in an inert atmosphere tube furnace for calcination at 340°C, with a heating rate of 1.5°C / min and a calcination time of 6h to obtain a sodium iron magnesium sulfate composite electrode material, wherein the sodium iron magnesium sulfate molecular formula is Na 2.6 Mg 0.2 Fe 1.5 (SO4)3, the flash graphene content is 7.01wt%.

[0042] The XRD pattern of the above-mentioned sodium iron magnesium sulfate composite electrode material is as follows: Figure 4 As shown in Figure 1, the XRD diffraction peak of the material is sharp and no impurity phase appears; the corresponding scanning electron microscope image of the sodium magnesium iron sulfate composite electrode material is as follows: Figure 5 As shown, it can be clearly seen that the crystal size of sodium magnesium ferric sulfate is uniform, and the particle size is between 1-5 microns;

[0043] Transmission electron microscopy image of sodium iron magnesium sulfate composite electrode material, such as Figure 6 As shown, obvious lattice fringes of sodium magnesium iron sulfate single crystal can be observed, and the hexagonal single crystal diffraction spots of selected area electron diffraction further prove the single crystal structure of the material.

[0044] Example 4

[0045] S1, heat-treat 41.70 g of ferrous sulfate heptahydrate in an inert atmosphere tube furnace at 250° C. for 6 h to obtain 22.80 g of anhydrous ferrous sulfate.

[0046] S2, 22.80 g of anhydrous ferrous sulfate, 18.46 g of anhydrous sodium sulfate, 2.72 g of anhydrous calcium sulfate and 2.35 g of flash graphene are ball-milled in an inert atmosphere ball mill for 4 h to obtain a calcined precursor.

[0047] S3, placing the calcined precursor in an inert atmosphere tube furnace for calcination at 350°C, with a heating rate of 1.5°C / min and a calcination time of 6h to obtain a sodium-calcium-iron sulfate composite electrode material, wherein the sodium-calcium-iron sulfate molecular formula is Na 2.6 Ca 0.2 Fe 1.5 (SO4)3, the flash graphene content is 6.96wt%.

[0048] The rate performance diagram of the above-mentioned sodium-calcium-iron sulfate composite electrode material is as follows: Figure 7 As shown, the results show that the material still has a cycle capacity of more than 80 mAh / g at a large rate of 100C, demonstrating excellent rate performance.

[0049] Example 5

[0050] S1, heat-treat 41.70 g of ferrous sulfate heptahydrate in an inert atmosphere tube furnace at 250° C. for 6 h to obtain 22.80 g of anhydrous ferrous sulfate.

[0051] S2, 22.80 g of anhydrous ferrous sulfate, 18.46 g of anhydrous sodium sulfate, 1.2 g of anhydrous magnesium sulfate, 1.36 g of anhydrous calcium sulfate and 7.91 g of flash graphene were ball-milled in an inert atmosphere ball mill for 4 h to obtain a calcined precursor.

[0052] S3, placing the calcined precursor in an inert atmosphere tube furnace for calcining at 350°C, with a heating rate of 1.5°C / min and a calcining time of 6h to obtain a sodium-magnesium-calcium-iron sulfate composite electrode material, wherein the sodium-magnesium-calcium-iron sulfate molecular formula is Na 2.6 Mg 0.1 Ca 0.1 Fe 1.5 (SO4)3, the flash graphene content is 12.36wt%.

[0053] Example 6

[0054] S1, heat-treat 30.58 g of ferrous sulfate heptahydrate in an inert atmosphere tube furnace at 250° C. for 8 h to obtain 16.72 g of anhydrous ferrous sulfate.

[0055] S2, 16.72 g of anhydrous ferrous sulfate, 19.88 g of anhydrous sodium sulfate, 1.2 g of anhydrous magnesium sulfate, 5.44 g of anhydrous calcium sulfate and 2.59 g of flash graphene were ball-milled in an inert atmosphere ball mill for 12 h to obtain a calcined precursor.

[0056] S3, placing the calcined precursor in an inert atmosphere tube furnace for calcination at 380°C, with a heating rate of 1.5°C / min and a calcination time of 15h to obtain a sodium-magnesium-calcium-iron sulfate composite electrode material, wherein the sodium-magnesium-calcium-iron sulfate molecular formula is Na 2.8 Mg 0.1 Ca 0.4 Fe 1.1 (SO4)3, the flash graphene content is 5.65wt%.

[0057] The long-term cycle performance diagram of the above-mentioned iron magnesium calcium sodium sulfate composite electrode material is as follows: Figure 8 As shown, the results show that the material can still maintain a capacity retention rate of more than 90% after 7000 cycles at a high current of 100C, and has particularly excellent high-rate cycle stability.

[0058] In summary, the successful doping of Mg and / or Ca can change the electron cloud distribution of Fe atoms in the lattice, improve the delocalization ability of Fe outer electrons, effectively reduce the band gap width of sodium iron sulfate, and significantly improve its conductivity. Combined with the good conductive network of flash graphene, the conductivity of the composite material can be significantly improved.

[0059] The contents not described in detail in the specification of the present invention belong to the prior art known to the professional and technical personnel in the field. Although the illustrative specific embodiments of the present invention are described above to facilitate the understanding of the present invention by the technical personnel in the field, it should be clear that the present invention is not limited to the scope of the specific embodiments. For the ordinary technical personnel in the field, as long as various changes are within the spirit and scope of the present invention defined and determined by the attached claims, these changes are obvious, and all inventions and creations using the concept of the present invention are protected.

Claims

1. A high-rate sodium-ion battery cathode material, comprising magnesium iron sulfate and / or calcium sodium single crystal particles and flash graphene; the chemical formula of the magnesium iron sulfate and / or calcium sodium is: Na 2+2x M y Fe 2-x-y (SO4)3, wherein x ranges from 0.25 to 0.45, y ranges from 0.05 to 0.6, and M is Mg and / or Ca element.

2. A high-rate sodium ion battery positive electrode material according to claim 1, characterized in that: In the chemical formula of magnesium iron sulfate and / or calcium sodium, when M is the coexistence of Mg and Ca, the molar fractions of Mg and Ca in M ​​are: Mg 0.01-0.99, Ca 0.99-0.

01.

3. A high-rate sodium ion battery positive electrode material according to claim 1, characterized in that: The mass ratio of the magnesium ferric sulfate and / or calcium sodium single crystal particles and the flashed graphene is: 85-97% of the magnesium ferric sulfate and / or calcium sodium single crystal particles and 3-15% of the flashed graphene.

4. A high-rate sodium ion battery positive electrode material according to claim 1, characterized in that: The Joule heat treatment temperature of the flash graphene is between 3100 and 3300 K, and the time is less than 1 second.

5. The method for preparing a high-rate sodium ion battery positive electrode material according to claim 1, characterized in that: The following steps are involved: S1, subjecting ferrous sulfate heptahydrate to heat treatment in an inert atmosphere tube furnace to obtain anhydrous ferrous sulfate; S2, ball milling anhydrous ferrous sulfate, anhydrous sodium sulfate, anhydrous magnesium sulfate and / or anhydrous calcium sulfate and flash graphene in an inert atmosphere ball mill for 4 to 15 hours to obtain a calcined precursor; S3, placing the calcined precursor in an inert atmosphere tube furnace for calcining at 320-380° C., with a heating rate of 1.5-2° C. / min and a calcining time of 6-15 h to obtain magnesium iron sulfate and / or calcium sodium composite electrode materials.

6. The method for preparing a high-rate sodium ion battery positive electrode material according to claim 5, characterized in that: In step 1, the heat treatment temperature is 250° C. and the time is 4 to 12 hours.

7. The method for preparing a high-rate sodium ion battery positive electrode material according to claim 5, characterized in that: In the step 2, the gas filled in the inert atmosphere ball milling jar is argon or nitrogen, and the ball milling time is 4 to 12 hours.

Citation Information

Patent Citations

  • Sodium ion positive electrode material, preparation method and sodium ion battery

    CN118472225A

  • Sodium ferric sulfate / carbon composite material as well as preparation method and application thereof

    CN118851274A